Innovative public library services during the COVID-19 pandemic: Application and revision of social innovation typology - Syn, Sue Yeon; Sinn, Donghee; Kim, Sujin (Library & information science research, 2023)
Public libraries needed to quickly address the new challenges brought by COVID-19 to continue their services. This study aimed to understand innovative public library services during the pandemic and provide a typology that represent their services. Twitter messages of 12 large public libraries were analyzed to identify library services. A total of 751 Tweets were coded with thematic tags by service types and innovative approaches. Using the social innovation typology by Winberry and Potnis (2021), their typology was revised to show public libraries' innovative services under the emergency circumstances. The findings suggested significant differences within social innovation categories and newly emerged themes. The revised social innovation typology developed from Twitter data during the pandemic includes nine major categories of public libraries' innovative service types and provides updated insights into how public libraries continue to serve as important community resources using innovative approaches. The revised typology will be useful for future research in describing future innovation and assessing the endurance of pandemic-era service innovations. •The findings suggest a need for expansion of the social innovation typology for public libraries' innovative services.•This Twitter study highlights that public library innovation leads to ensure service continuity in the pandemic.•The tweets of different periods demonstrated that library innovation mainly changes in diverse service modalities.•Public libraries emphasize community as a focal point and play an important role as public educational centers.•Collaboration with other institutions is one key aspect of innovative public library services.